2018
DOI: 10.1177/0963689717738786
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Differentiation Properties of Amniotic Cells Are Retained After Immobilization in Pectin Gel

Abstract: Mesenchymal stromal cells from the human amniotic membrane (i.e., human amniotic mesenchymal stromal cells [hAMSCs]) of term placenta are increasingly attracting attention for their applications in regenerative medicine. Osteochondral defects represent a major clinical problem with lifelong chronic pain and compromised quality of life. Great promise for osteochondral regeneration is held in hydrogel-based constructs that have a flexible composition and mimic the physiological structure of cartilage. Cell loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The intrinsic immune‐modulatory properties of hAMSCs were confirmed by immunohistochemical results that showed no significant activation of the adaptive immunity (CD4 and CD8), thus confirming the inability of these cells to induce a T‐cell response in accordance with Silini et al (2018). Furthermore, significant activation of the innate immunity was observed (CD45 and CD68).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The intrinsic immune‐modulatory properties of hAMSCs were confirmed by immunohistochemical results that showed no significant activation of the adaptive immunity (CD4 and CD8), thus confirming the inability of these cells to induce a T‐cell response in accordance with Silini et al (2018). Furthermore, significant activation of the innate immunity was observed (CD45 and CD68).…”
Section: Discussionsupporting
confidence: 79%
“…Pectin microspheres were studied for 3D culture of bone cells, showing interesting properties for cell viability, metabolic activity and differentiation (Munarin et al, 2010(Munarin et al, , 2011. The pectin gel used in the present study was investigated in preliminary experiments with hAMSCs for the first time, confirming increased cell viability, biocompatibility, ability to differentiate toward osteogenic commitment, and retaining the ability to reduce T cell proliferation (Farè et al, 2015;Silini et al, 2018). As the PU/VAC/PECT scaffold showed the pectin degradation after 4 days of incubation in vitro, cells previously embedded in can be release in the defect site, pro- The intrinsic immune-modulatory properties of hAMSCs were confirmed by immunohistochemical results that showed no significant activation of the adaptive immunity (CD4 and CD8), thus confirming the inability of these cells to induce a T-cell response in accordance with Silini et al (2018).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Human dental pulp stem cells (hDPSCs) which were isolated and characterized in a previous study [39] were a kind gift from Prof. Dr. Menemşe Gümüşderelioğlu, from Hacettepe University, Turkey. The cells were cultured in 15% (v/v) fetal bovine serum (FBS, Biowest, France) including alpha-Minimum Essential Medium (α-MEM, Biochrom, Germany).…”
Section: Human Dental Pulp Stem Cells Culturementioning
confidence: 99%
“…In a study, human amniotic membrane MSCs were cultured in hydroxyapatite/LM pectin composite gel structure. It was shown that MSCs preserved their osteogenic differentiation capacity and inhibition of T cell proliferation in the presence of LM pectin, also they did not trigger immune response [39]. Pectin/chitosan membrane can provide attachment, adhesion and proliferation of adipose-derived stem cells (ADSCs) [40].…”
mentioning
confidence: 99%